The Effect of Bicycle Training Program on Aerobic and Anaerobic Performance - Şükran Arıkan; Serkan Revan (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to determine the effect of cycling exercise program applied to young adults for eight weeks on aerobic and anaerobic performance. Fourteen volunteer, non-smokers, moderately active men aged between 19-23 participated in the study. The aerobic performance of the participants before and after the training program was determined by 20-meter shuttle running test and their anaerobic performance was determined by Wingate anaerobic power test. The training program consisted of 40-60 minutes cycle ergometer exercise performed 3 times weekly for 8 weeks at a work load corresponding to 60-80% of the maximal heart rate. The pre-post data were compared using the Wilcoxon paired signed ranks test. According to the findings of the study, there was no significant difference in body weight, body mass index, minimum strength and fatigue index values (p gt;0,05), while there was a significant difference in the maximum oxygen uptake (VO2max), peak power and average power values in the pre-test and post-test scores (p lt;0,05). As a result, it can be said that regular cycling exercises improve aerobic and anaerobic performance positively.